2014
DOI: 10.1111/pai.12211
|View full text |Cite
|
Sign up to set email alerts
|

Higher latitude and lower solar radiation influence on anaphylaxis in Chilean children

Abstract: Background Recent studies suggest an association between higher latitude, a proxy of vitamin D (VD) status, and allergic diseases. Chile provides an ideal setting to study this association due to its latitude span and high rates of VD deficiency in southern regions. The aim of this study is to explore the associations of latitude and solar radiation with anaphylaxis admission rates. Methods We reviewed anaphylaxis admissions in Chile’s hospital discharge database between 2001 and 2010 and investigated associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
1
24
0
4
Order By: Relevance
“…Specifically, we recently reported that the rate of U.S. pediatric hospitalizations for FIA between 2000 and 2009 increased dramatically nationwide but was more than twice as high in the north-east compared with the south [12 & ]. Outside the United States, similar patterns have also been described in FIA hospitalization rates both in Chile [13] and in Italy [14]. It should, however, be recognized that not all studies have been equally supportive.…”
Section: Sunlight and Food Allergymentioning
confidence: 69%
“…Specifically, we recently reported that the rate of U.S. pediatric hospitalizations for FIA between 2000 and 2009 increased dramatically nationwide but was more than twice as high in the north-east compared with the south [12 & ]. Outside the United States, similar patterns have also been described in FIA hospitalization rates both in Chile [13] and in Italy [14]. It should, however, be recognized that not all studies have been equally supportive.…”
Section: Sunlight and Food Allergymentioning
confidence: 69%
“…Therefore if vitamin D is truly important in asthmatic disease we can expect higher asthma incidence at higher latitude. Indeed, several reports have suggested that latitude is positively correlated to asthma [2,56,87,95] and allergy [80]. However, not all ecological studies demonstrate this effect, with some studies noting no interaction [81,114], and others still an increased risk at lower latitude [131,151,170,176,187].…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…There are numerous studies which indicate that there may be an association between low vitamin D levels and anaphylaxis, allergies and asthma [19][20][21]. While there are other studies that have not found any association between vitamin D and atopy or asthma [15].…”
Section: Discussionmentioning
confidence: 98%